GENETIC DIVERGENCE IN ASH GOURD (Benincasa hispida Thunb.) (Bangladesh Journal of Plant Breeding and Genetics, 2013)
Genetic divergence among 46 ash gourd genotypes from different origins was investigated to select the parents for hybridization using Mahalanobis D2 statistics. Though the genotypes grouped into seven clusters, the pattern of distribution of the genotypes into different clusters were random indicating that the geographical isolation was not always related to genetic diversity. Characters like fruit weight, fruits per plant, days to first male flower and nodes for first male flower contributed considerably to the total divergence. Maximum inter-cluster distance between cluster III and IV indicating wide genetic divergence between the genotypes of these two clusters (cluster III and IV followed by cluster IV and VII). However, the intra-cluster distances were smaller than inter-cluster distances. Thus, crossing between the genotypes of these two groups (cluster III and IV) would produce high heterotic progeny and may produce new recombinants with desired traits.DOI: http://dx.doi.org/10.3329/bjpbg.v20i1.17014